The combined use of Bacillus thuringiensis and Nesidiocoris tenuis against the tomato borer Tuta absoluta - Mollá-Hernández, Óscar; González-Cabrera, Joel; Urbaneja, Alberto (2017)
Since Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) was first detected at the end of 2006 in the Mediterranean Basin, several endemic natural enemies have been reported to prey on this exotic pest. The predator Nesidiocoris tenuis Reuter (Hemiptera: Miridae) can regulate T. absoluta populations, because it is able to prey efficiently on T. absoluta eggs. Furthermore, previous studies have demonstrated that first-instar larvae of T. absoluta are highly susceptible to Bacillus thuringiensis (Bt) treatments. In this work, we tested the combination of both approaches under greenhouse conditions. B. thuringiensis formulations were sprayed weekly for two months, three months or throughout the growing cycle, and in all cases, one N. tenuis per plant was also released. Control plants were completely destroyed by the infestation levels reached by T. absoluta. In contrast, all treatments based on B. thuringiensis treatments and releases of N. tenuis reduced leaf damage by more than 97% when compared to the untreated control, with no significant differences among them. Furthermore, yield in the control plants was significantly reduced when compared with all Bt-N. tenuis treatments. Our results demonstrate that when B. thuringiensis treatments are applied immediately after the initial detection of T. absoluta on plants, they do not interfere with N. tenuis establishment in the crop because T. absoluta eggs are available. According to our data, treatments with B. thuringiensis later in the growing season would no longer be necessary because mirids alone would control the pest.